Financing of private hydropower projects - Head, Chris; World Bank (Washington World Bank, 2000)
Financing of private hydropower examines ten hydropower projects with private participation in five developing countries the philippines Lao PDR, Nepal,Turkey and Brazil.Although hydro schemes could be unique and different including multi and single purpo
Keywords: Water-Power; Natural resources; Water resource development